The remarkable effect of oxygen on the N2 selectivity of water catalytic denitrification by hydrogen - Constantinou, Costas L.; Efstathiou, Angelos M.; Costa, Costas (My University, 2007)
The selective catalytic reduction of nitrates (NO3-) in pure water toward N2 formation by the use of gaseous H2 and in the presence of O2 (air) at 1 atm total pressure and 25 Β°C has been investigated over Pdβ ’Cu supported on various mixed metal oxides, x wt % MOx/Ξ³-Al2O3 (MOx = CeO2, SrO, Mn2O3, Cr2O3, Y2O3, and TiO2). It is demonstrated for the first time that a remarkable improvement in N2 reaction selectivity (by 80 percentage units) can be achieved when oxygen is present in the reducing feed gas stream. In particular, significantly lower reaction selectivities toward NH4+ and NO2- can be obtained, whereas the rate of NO3- conversion is not significantly affected. Moreover, it was shown that the same effect is obtained over the Pdβ ’Cu-supported catalysts irrespective to the chemical composition of support and the initial concentration of nitrates in water used. The Pdβ ’Cu clusters supported on 4.8 wt%TiO2/Ξ³-Al2O3 resulted in a solid with the best catalytic behavior compared with the rest of supports examined, both in the presence and in the absence of oxygen in the reducing feed gas stream. DRIFTS studies performed following catalytic reduction by H2 of NO3- in water revealed that the presence of TiO2 in the Pdβ ’Cu/TiO2β ’Al2O3 system enhanced the reactivity of adsorbed bidentate nitrate species toward H2. Nitrosyl species adsorbed on the alumina and titania support surfaces are considered as active intermediate species of the selective catalytic reduction of NO3- by H2 in water. Pdβ ’Cu/TiO2β ’Al2O3 appears to be the most selective catalyst ever reported in the literature for the reduction of nitrates present in pure water into N2 by a reducing gas mixture of H2/air.
Keywords: Oxygen; Water chemistry; Catalysts; Hydrogen